1992
DOI: 10.1111/j.1365-2842.1992.tb01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in signs and symptoms from masticatory and other muscles in 19‐year‐old individuals

Abstract: Pain and tenderness of masticatory muscles are often related to muscle tenderness elsewhere in the body. It has been shown that women are more prone to musculoskeletal disorders than men. We sought to determine whether sex differences of muscular symptoms were established by the age of 19. The subjects comprised 51 boys and girls who received a questionnaire regarding the function of their masticatory system, frequency of headache, and neck, shoulder and low back pain. Their masticatory system was examined, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
0
12
0
7
Order By: Relevance
“…It has been demonstrated that there are some gender differences in the jaw musculature's fiber composition (28), as well as in EMG output (29). These findings might partly explain earlier exhaustion and pain in the musculature of females than in that of males (30). Hanson (31) has suggested that TM joints in women are more stable morphologically, whereas in men they are more adaptive even before condylar growth has ceased.…”
Section: Discussionmentioning
confidence: 91%
“…It has been demonstrated that there are some gender differences in the jaw musculature's fiber composition (28), as well as in EMG output (29). These findings might partly explain earlier exhaustion and pain in the musculature of females than in that of males (30). Hanson (31) has suggested that TM joints in women are more stable morphologically, whereas in men they are more adaptive even before condylar growth has ceased.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, current theories of TMD etiology agree that muscle hyperactivity is probably the final common pathway leading to TMD pain symptoms (Rugh, 1981;Zarb and Mohl, 1988). Since TMD are more common in females (Locker and Slade, 1988;Huber and Hall, 1990;Bakke and M0ller, 1992;Krogstad et al, 1992;De Kanter et al, 1993;however, cf. Duckro et al, 1990;Glass et al, 1993), this means that sex-specific risk factors associated with oral function predispose women to developing TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Duckro et al, 1990;Glass et al, 1993). Furthermore, there is evidence that TMD symptoms are precipitated or perpetuated by functional and parafunctional habits (Christensen, 1971;Trenouth, 1979;Davidson and Mohl, 1987;Klineberg, 1988;Rugh and Harlan, 1988;Schiffman et al, 1992;Bakke and M0ller, 1992;Krogstad et al, 1992; however, cf. Seligman and Pullinger, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por ejemplo, Sandoval et al (5) reportaron una prevalencia de 13% en la población de Chile, con mayor predisposición en el sexo femenino; Krogstad et al (6), Listet et al (7) y Magnusson et al (8) mencionaron índices de prevalencia para la población general que van del 20% al 70%, lo cual concuerda con Corsini (9) y Larrucea (10). Por otra parte, en muestras de individuos menores de 18 años, principalmente de países europeos, se han reportado prevalencias muy variables, que van desde el 4% hasta el 77% (Tabla 1).…”
Section: Datos Epidemiológicosunclassified